Preface: Unsolved Problems of Magnetospheric Physics - Stepanova, M (Blackwell Publishing Ltd, 2016)
The Unsolved Problems of Magnetospheric Physics Workshop was held in September 2015 in Scarborough, UK. In contrast to most other meetings, people were specifically asked not to present and discuss their recent results. Rather, they were asked to bring their opinions and thoughts on unsolved problems to the meeting. Short presentations were encouraged after which the audience would debate and discuss definitions of the problems and how they could be overcome. Were new observations required? New missions? Or simply did the community need to work better together to resolve pertinent and outstanding science questions? Around 50% of the meeting schedule was devoted to discussion sessions on these topics. ©2016. American Geophysical Union. All Rights Reserved.